Performance on the dementia rating scale in Parkinson's disease with dementia and dementia with Lewy bodies: comparison with progressive supranuclear palsy and Alzheimer's disease. Issue 9 (21st August 2003) - Aarsland, D; Litvan, I; Salmon, D; Galasko, D; Wentzel-Larsen, T; Larsen, J P
Abstract : Background: The relation between dementia with Lewy bodies (DLB) and Parkinson's disease with dementia (PDD) is unknown. Objectives: To compare the cognitive profiles of patients with DLB and PDD, and compare those with the performance of patients with a subcortical dementia (progressive supranuclear palsy) and a cortical dementia (Alzheimer's disease). Design: Survey of cognitive features. Setting: General community in Rogaland county, Norway, and a university dementia and movement disorder research centre in the USA. Patients: 60 patients with DLB, 35 with PDD, 49 with progressive supranuclear palsy, and 29 with Alzheimer's disease, diagnosed by either standardised clinical procedures and criteria (all PDD and Alzheimer cases and 76% of cases of progressive supranuclear palsy), or necropsy (all DLB cases and 24% of cases of progressive supranuclear palsy). Level of dementia severity was matched using the total score on the dementia rating scale adjusted for age and education. Main outcome measures: Dementia rating scale subscores corrected for age. Results: No significant differences between the dementia rating scale subscores in the PDD and DLB groups were found in the severely demented patients; in patients with mild to moderate dementia the conceptualisation subscore was higher in PDD than in DLB (p = 0.03). Compared with Alzheimer's disease, PDD and DLB had higher memory subscores (p < 0.001) but lower initiation and perseveration (p = 0.008 and p=0.021) and construction subscores (p = 0.009 and p = 0.001). DLB patients had a lower conceptualisation subscore (p = 0.004). Compared with progressive supranuclear palsy, PDD and DLB patients had lower memory subscores (p < 0.001). Conclusions: The cognitive profiles of patients with DLB and PDD were similar, but they differed from those of patients with Alzheimer's disease and progressive supranuclear palsy. The cognitive pattern in DLB and PDD probably reflects the superimposition of subcortical deficits upon deficits typically associated with Alzheimer's disease.